1999
DOI: 10.1046/j.1365-3083.1999.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Protein Antigen Encoded by a Mycobacterium tuberculosis‐Specific RD1 Region Gene

Abstract: A genomic DNA region, designated RD1, that is present in virulent and clinical strains of Mycobacterium tuberculosis and M. bovis, has been shown to be deleted in bacillus Calmette Guérin (BCG). The DNA segments corresponding to three open reading frames (ORFs: ORF‐10, ORF‐14 and ORF‐15) of the RD1 region, that are deleted in BCG strains, were amplified from M. tuberculosis genomic DNA by polymerase chain reaction (PCR), subcloned into pGEX‐4T vector system and expressed in Escherichia coli as fusion proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 27 publications
3
69
0
Order By: Relevance
“…However, obtaining full-length purified RD1 proteins that are free of contaminants, either from cultures of M. tuberculosis or using recombinant expression and purification technologies, is technically demanding and quite cumbersome (31)(32)(33). Therefore, to overcome the problems associated with obtaining full-length proteins, pools of synthetic peptides corresponding to each RD1 ORF were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, obtaining full-length purified RD1 proteins that are free of contaminants, either from cultures of M. tuberculosis or using recombinant expression and purification technologies, is technically demanding and quite cumbersome (31)(32)(33). Therefore, to overcome the problems associated with obtaining full-length proteins, pools of synthetic peptides corresponding to each RD1 ORF were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When tested with human serum, ORF14 was found to be a major antigen recognized by antibodies in sera of TB patients (1). Interestingly, ORF14 was predicted only by Amoudy et al but not by others (7) ( Table 1), and several studies have confirmed that ORF14 is a real protein coding gene of M. tuberculosis that is expressed under both in vitro and in vivo growth conditions (1,8,11). These findings suggest that to identify additional antigens of diagnostic and/or vaccine relevance, a systematic screening of all RD1 ORF proteins should be performed for immunological reactivity.…”
mentioning
confidence: 97%
“…However, obtaining full-length proteins from cultures of pathogenic M. tuberculosis is extremely hazardous and technically demanding (39). On the other hand, the production of purified recombinant mycobacterial proteins has often been notoriously difficult in E. coli (1,2,12). To overcome the problems associated with the expression and purification of recombinant mycobacterial proteins, pools of overlapping synthetic peptides have been successfully used in the past to replace recombinant or natural M. tuberculosis proteins in Th1 cell assays (40,41,55).…”
Section: Discussionmentioning
confidence: 99%